Pentanuclear lanthanide pyramids based on thiacalix[4]arene ligand exhibiting slow magnetic relaxation1. Issue 35 (21st September 2015) - Ge, Jing-Yuan; Ru, Jing; Gao, Feng; Song, You; Zhou, Xin-Hui; Zuo, Jing-Lin
<x xml:space="preserve">Abstract</x> Six pentanuclear LnIII clusters have been isolated based on thiacalix[4]arene ligand for the first time. Two Dy5 clusters feature distinct slow magnetic relaxation, which is affected presumably by the ligand, field molecular symmetry and coordination geometries of lanthanide ions.